Dam Break Analysis of Sermo Dam - Maria Sumira; Evi Anggraheni; Rian Mantasa Salve Prastica (Journal of the Civil Engineering Forum, 2023)
Sermo Dam is located in the Special Region of Yogyakarta and serves multiple purposes including providing drinking water, supplementing irrigation systems in the Kalibawang area, and flood control. According to data published by the World Commission, 60% of mitigation measures taken to overcome the impact of dam structure failures are unsuccessful. The simulation of dam failure serves as a crucial aspect of flood mitigation plans and strategies because it is more destructive than natural flood waves. This research used HEC-RAS 5.0.7 to examine the flood inundation mapping and simulate dam failure in two dimensions. However, Dam Break Analysis was adopted to provide a Dam Emergency Action Plan Guide to guide managers and the community. The overtopping scenario was adapted to model the failure of the Sermo Dam based on the frequent occurrence of heavy and extreme precipitation in the affected area. Data were analyzed using unsteady flow and PMF discharge with peak inflow discharge of 1276.6 m³/s, which result in an inundation area of 9394 hectares and a maximum flood height of 17 m. Dam failure-induced floods tend to potentially affect eight sub-districts including Kokap, Pengasih, Sentolo, Wates, Panjatan, Galur, Lendah, and Temon. The piping scenario is also considered based on the potential damage that tends to occur. In the piping scenario, the biggest flooding area was 5112 hectares with a maximum flood height of 13 m. About six sub-districts are potentially affected by dam failure-induced floods with Kokap and Sentolo being excluded from the list.  Therefore, it is crucial to establish early warning systems and infrastructure to mitigate disaster risks. The results of this research can also inform evacuation planning, damage estimation, and post-flood rehabilitation efforts in the affected areas.